Productive Waqf and People Economic Empowerment in Indonesia - Gatot Bintoro Putro Aji (Journal of Islamic Business and Economic Review, 2020)
Productive empowerment of waqf is an effort to develop and manage waqf assets through various empowerment programs so that their usefulness is sustainable and waqf can be distributed evenly. In 2019, the Indonesian Waqf Board (BWI) stated that the potential of waqf assets in Indonesia annually reaches 2000 trillion with waqf land area reaching 420,000 hectares. Meanwhile, based on data from the Ministry of Religion Waqf Information System (2019), the area of waqf land in Indonesia reached 51,480.01 hectares spread over 382,722 locations. Of this amount, only 61.09% of them have been certified and 73% of waqf assets are intended only for places of worshipand not yet productive.The purpose of this study is to find out what efforts can be made in optimizing the empowerment of productive waqf in improving the economic welfare of the community. There are several important aspects as an effort in realizing the success of the community's economic prosperity through the empowerment of productive waqf, that is: Optimizing the role of Nazir and Optimizing the empowerment of productive waqf.